Comparing the protective effects of Resveratrol, Curcumin, and Sulforaphane against Doxorubicin-mediated inflammation in macrophages - Saleh, Haidy Amr Abdelfatah (AUC Knowledge Fountain, 2020)
Doxorubicin (DOX) anti-tumor activity is accompanied by severe side effects such as cardiotoxicity and cardiomyopathy. These side effects are hypothesized to be mediated through doxorubicin induced inflammation. The aim of the current study, therefore, was to compare the effect of three naturally derived compounds with anti-inflammatory effects namely, curcumin (CUR), resveratrol (RES) and sulforaphane (SFN) against doxorubicin-mediated inflammation through affecting TLR4 signaling pathway in the murine macrophage cell line RAW264.7 stimulated with Lipopolysaccharide/Interferon-gamma (LPS/IFN- γ). In present study, RAW264.7 cells were stimulated with LPS/IFN-γ at a concentration of 10 ng/10 U/mL in the absence and presence of DOX (0.1 µM) plus increasing concentrations of CUR, RES or SFN (5 - 20 µM) for 24 h. Cell lysates of LPS/IFN- γ stimulated RAW264.7 macrophages were collected and assayed for the mRNA expression of tumor necrosis factor alpha (TNF-), interleukin-6 (IL-6), inducible nitric oxide synthase (iNOS) and toll like receptor 4 (TLR4) and miRNA expression of miR-146a, miR-155, and miR-21 levels using real-time PCR. Furthermore, TNF- and IL-6 protein were characterized in culture supernatants via enzyme-linked immunosorbent assay (ELISA). Nitric oxide (NO) production was determined using the Griess assay and cell viability was assessed via 3-(4, 5- dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Our results showed that LPS/IFN-γ with/out DOX significantly induced TNF-, IL-6, and iNOS, and downregulated TLR-4 mRNA expression levels. Also, it upregulated miR-146a and miR-155, with no significant effect on miR-21. DOX alone was unable to induce any of these markers. Moreover, the LPS/IFN-γ mediated upregulation of TNF- and IL-6 on the mRNA level was further translated to protein levels. Additionally, LPS/IFN- γ mediated induction of iNOS resulted in a significant increase in NO production that persists in the presence of DOX. Upon treating the LPS/IFN-γ stimulated macrophages with the different concentrations of the three naturally derived compounds, SFN was the only compound to show a significant decrease in LPS/IFN-γ-induced TNF-, IL-6, and iNOS mRNA expression levels. This effect of SFN in response to LPS/IFN-γ stimulation was conserved at the TNF- and IL- 6 protein levels and NO production in the absence and presence of DOX. Interestingly, SFN significantly inhibited the LPS/IFN-γ mediated induction of miR-146a and miR-155 miRNA levels in RAW 264.7 cells. Last but not least, the SFN inhibition of the inflammation markers and miRNAs was not due to any cytotoxic effects as evident by MTT assay. Our findings suggest that SFN, compared to CUR or RES, significantly exerted an anti-inflammatory response in RAW264.7 cells stimulated with LPS/IFN-γ with/out DOX. This effect was confirmed on the transcriptional and post-transcriptional levels. Altogether, these findings provide an important rationale to utilizing SFN as a potential adjuvant for the prevention and/or treatment of DOX mediated cardiotoxicity that may be in part due to inflammation. The present study, therefore, can be implied in future clinical trials.